Overexpression of MdMIPS1 enhances drought tolerance and water-use efficiency in apple - Ling-yu HU; Hong YUE; Jing-yun ZHANG; Yang-tian-su LI; Xiao-qing GONG; Kun ZHOU; Feng-wang MA (Journal of Integrative Agriculture)
Myo-inositol and its derivatives play important roles in the tolerance of higher plants to abiotic stresses, and myo-inositol-1-phosphate synthase (MIPS) is the rate-limiting enzyme in myo-inositol biosynthesis. In this study, we found that increased myo-inositol biosynthesis enhanced drought tolerance in MdMIPS1-overexpressing apple lines under short-term progressive drought stress. The effect of myo-inositol appeared to be mediated by the increased accumulation of osmoprotectants such as glucose, sucrose, and proline, and by the increased activities of antioxidant enzymes that eliminate reactive oxygen species. Moreover, enhanced water-use efficiency (WUE) was observed in MdMIPS1-overexpressing apple lines under long-term moderate water deficit conditions that mimicked the water availability in the soil of the Loess Plateau. Enhanced WUE may have been associated with the synergistic regulation of osmotic balance and stomatal aperture mediated by increased myo-inositol biosynthesis. Taken together, our findings shed light on the positive effects of MdMIPS1-mediated myo-inositol biosynthesis on drought tolerance and WUE in apple.